Strategi Komunikasi Guru Untuk Anak Usia Dini Dengan Speech Delay - Anggraini, Elya Siska; Lubis, Siti Khodijah; Sitangggang, Agnesia; Mairianta, Beatriz; Lubis, Gustiana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Speech delay is one of the common language development disorders occurring in early childhood and can impact a child’s communication, social, and emotional abilities. This study aims to describe the communication strategies applied by early childhood education (PAUD) teachers in assisting children with speech delay. The research uses a descriptive qualitative approach, with two 6-year-old children showing symptoms of speech delay as subjects at a private kindergarten in Medan City. Data collection was conducted through direct observation of verbal and non-verbal interactions during the learning process. The results indicate that the characteristics of speech delay differ between the children; one child tends to be socially passive, while the other is active but has articulation difficulties. Teachers use various communication strategies, such as visual media, positive reinforcement, and individualized approaches to stimulate the children’s language abilities. The findings also emphasize the importance of collaboration between teachers and parents and early detection to ensure more effective and comprehensive intervention.